The impact of Islamic thought in contemporary Malaysian society with special reference to sociology - Md. Noon, Hazizan (2017)
The aim of this paper is to elucidate the status, roles and influence of Islam in what is today’s known as the contemporary Malaysian society. The paper is based on reference to some prevailing works which are consolidated to meet the need of the Conference’s theme namely “Sociology in Islamic Geographies”. The main question to answer is, to what extend Islam has been influential in the Malaysia’s educational affairs particularly in the field of sociology. Due to various limitations, the paper only touches on some major themes and portrays significant manifestations for each theme with the final reference to the current practice of the Department of Sociology and Anthropology at one of Malaysia’s Islamic higher learning institutions. To set a relevant historical context prior to the discussion, the paper firstly provides a brief historical recital of the coming of Islam to the Malay Archipelago and its consequences upon the nation’s various institutions and traditions - religious, literary, educational and others. It then presents an overview of its status and influence in the multi-racial and multi- religious society particularly after Malaysia regained its independence from the British in 1957. This part is crucial because the legal provisions regarding Islam in the Federation Constitution particularly Part I Article 3 declares that “the Religion of the Federation” and this has set as the main starting point for any effort at explaining Islam in the aftermath of independence. Equally important in this context is what is known as the Rukunegara or Pillars of the Nation which makes ‘belief in God’ as its first pillar. It is within these historical, constitutional and national ideological contexts and frameworks that various discourses on issues regarding ethnicity, economics, religion, education, politics and others found their expressions in contemporary Malaysia. Due to the limitations of space, the paper only focuses on issues within educational domain with particular reference to the practice of the Department of Sociology and Anthropology of the International Islamic University Malaysia (IIUM) as an illustration. The study is qualitative and descriptive in nature with library research being used in soliciting and utilizing information from the prevailing works and literature. The paper concludes that the interplay between the desire or goal of realizing Islamic religious ideals and the complex socio-cultural realities of the Malaysian society has informed us of the varying degrees and modes of adaptation that allows this ‘religion of the Federation’ to prevail throughout history and find its way in offering Islamic religious values and input peacefully to the Malaysian people. The prevailing social stability among its multi-ethnic and multi-religious population has allowed both the constant and dynamic forces within Islamic teachings to be incorporated also in its educational affairs as demonstrated for instance by the establishment and operation of the IIUM’s Department of Sociology and Anthropology. This, in one way or the other, might have been reflective of the frequent reference to the need for securing public interest under the broad guise of maqasid al-shari’ah or the lofty goals of religion which currently also becomes one of the Government’s catchwords.